PENERAPAN PEMBELAJARAN MAKE A MATCH UNTUK MENINGKATAN HASIL BELAJAR PPKN KELAS X SMAN 1 SUNGAI RAYA - Hamidia Hamidia; Bambang Budi Utomo; Thomy Sastra Atmaja (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract This study alms to determine the effectiveness of the use of make a macth learning models on the learning outcomes of class X students on PPKn subject in kubu raya 1 Senior High School. The research method used is the experimental method with the from of research used is pre-experimental design. The research subject were25 students of class X IIS 1. The results of data analysis showed that student learning outcomes before and after being given treatment experienced significant differencesproven by the result of the average post-test seen before using the make a macth learning models which is 49,28. The result of the post-test average of students who were treated with make a macht method were increased by 80,56. Based on the test obtained sig(2-tailed) value of 0,000 according to the basic of decision making in the independent T-Test, it can be conclude that Ho is rejected and Ha is accepted. Which means there is a difference between the average pre-test and post-test. Keywords:Aplication, Civic Education, Learning Outcomes, Make A Macth.